1976
DOI: 10.1177/001872087601800407
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time as an Index of Traffic Sign Perception

Abstract: Verbal reaction times to identify and to classify 20 traffic sign messages were measured under three conditions-sign alone, sign plus visual loading task, and sign plus visual loading task plus visual distraction. Similar trends were found in the three experiments: reaction times were smaller for the classification task than for the identification task, smaller for warning than for regulatory signs, and smaller for verbal than for symbolic messages. Comparison of these reaction time data with on-the-road measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 1 publication
1
31
0
Order By: Relevance
“…This experiment attempted to simulate an actual driving condition In which the Interval between viewing a sign and acting upon It Is occupied with a driving task -a condition similar to many mining operations during which a miner must see and act upon a sign's message while continuing to perform a customary mining operation. In another experiment on highway symbols, Dewar, Ells, and Mundy (1976) found that reaction time was always shorter for symbols under both normal and degraded viewing conditions.…”
Section: Background Researchmentioning
confidence: 94%
See 2 more Smart Citations
“…This experiment attempted to simulate an actual driving condition In which the Interval between viewing a sign and acting upon It Is occupied with a driving task -a condition similar to many mining operations during which a miner must see and act upon a sign's message while continuing to perform a customary mining operation. In another experiment on highway symbols, Dewar, Ells, and Mundy (1976) found that reaction time was always shorter for symbols under both normal and degraded viewing conditions.…”
Section: Background Researchmentioning
confidence: 94%
“…Routine maintenance and repairs accounted for 59 percent and 23 percent of the injuries, respectively. Generally, the injury related to catching fingers, hands, arms, and upper extremities in a moving belt.…”
Section: Detailed Hazard Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate this filtering process the design of signs in guidance systems (like platform numbers or speed limits) is essential. Early studies in this regard are concerned with differential effects in traffic sign perception, like smaller reaction times for warning than for regulatory signs (Dewar et al 1976) and longer reaction times for extravert participants (Loo 1978). More recent research in this field (Ben-Bassat and Shinar 2006) could show that ergonomic design principles play an important role in the comprehension of traffic signs.…”
Section: Attention In Guidance Systems and Driver-environmentsmentioning
confidence: 99%
“…Symbols may also be superior to words under conditions of interference either by distraction from another task (King, 1975) or by visual interference or degradation (Dewar, Ells, & Mundy, 1976). These advantages of symbols over words may not be true under all conditions for all symbols, however.…”
Section: Symbolic Signsmentioning
confidence: 99%